Connecting the Dots: Translating the Vaginal Microbiome Into a Drug. (17th December 2020) - Lagenaur, Laurel A; Hemmerling, Anke; Chiu, Charles; Miller, Steve; Lee, Peter P; Cohen, Craig R; Parks, Thomas P
Abstract: A Lactobacillus -dominated vaginal microbiota (VMB) has been associated with health and considered an important host defense mechanism against urogenital infections. Conversely, depletion of lactobacilli and increased microbial diversity, amplifies the risk of adverse gynecologic and obstetric outcomes. A common clinical condition that exemplifies dysbiosis is bacterial vaginosis (BV). BV is currently treated with antibiotics, but frequently recurs, due in part to persistent dysbiosis and failure of lactobacilli to repopulate the vagina. New treatment options are needed to address BV. The VMB is relatively simple and optimally dominated by one or several species of Lactobacillus . Lactobacillus crispatus is strongly associated with vaginal health and depleted in dysbiosis. Replenishing the dysbiotic VMB with protective L. crispatus CTV-05 is a promising approach to prevent recurrent infections and improve women's health. Here we discuss confirmation of this approach with the microbiome-based biologic drug, LACTIN-V ( L. crispatus CTV-05), focusing on prevention of BV recurrence.